Outsourcing management information systems - Schniederjans, Marc J.; Schniederjans, Ashlyn M.; Schniederjans, Dara G. (Gale Reference., 2007)
"This book balances the positive outcomes of outsourcing, which have made it a popular management strategy with the negative to provide a more inclusive decision; it explores risk factors that have not yet been widely associated with this strategy. It focuses on the conceptual "what", "why", and "where" aspects of outsourcing as well as the methodological "how" aspects"--Provided by publisher.